Deflection of high-intensity pulsed ion beam in focusing magnetically insulated ion diode with a passive anode; Physics of Plasmas; Vol. 23, iss. 12 - Zhu Xiaopeng P.; Zhang Quanzhi; Ding L.; Zhang Z. C.; Yu N.; Pushkarev A. I. Aleksandr Ivanovich; Lei Ming Kai (2016, 2016)
Title screen